Efficacy and safety of post-discharge oral nutritional supplements for patients with gastric cancer undergoing gastrectomy: a meta-analysis of randomized controlled trials - Liang, Qiuman; Wang, Siyi; Wang, Beibei; Hong, Yanyan (Frontiers in Nutrition, 2025)
Objectives To report the first and largest systematic review and meta-analysis of randomized controlled trials (RCT) to evaluated the efficacy and safety of post-discharge oral nutritional supplements (ONS) for patients with gastric cancer undergoing gastrectomy. Design Systematic review and meta-analysis. Eligibility criteria for selecting studies RCT which evaluated the efficacy and/or safety of post-discharge ONS for patients with gastric cancer undergoing gastrectomy. Data sources We conducted a systematic literature retrieval via PubMed, Embase, Web of Science, and Cochrane until April, 2023 for relevant RCTs. Data analysis Outcomes of meta-analysis included absolute change of body weight, % change of body weight, absolute change of body composition, absolute change of laboratory parameters and adverse events. All the relevant data were analyzed by Review Manager 5.4.1 and Stata 15.1. Results 5 RCTs including 1,586 patients (804 in ONS group versus 782 in control group) were included for meta-analysis. The two groups were comparable in age, gender (male), weight at baseline, BMI at baseline, albumin at baseline, and hemoglobin at baseline. Meta-analysis revealed a significant lower absolute body weight loss (WMD: 0.75; 95% CI: 0.11, 1.40; p = 0.02) and % body weight loss (WMD: 1.15; 95% CI: 0.20, 2.11; p = 0.02) in the ONS group compared with the control (regular diet/dietary advice) group. Moreover, this study did not observe a significant difference between the two groups for adverse events rate (RR: 1.11; 95% CI: 0.81, 1.53; p = 0.52). Conclusion ONS was significantly effective and safe in improving postoperative weight loss for patients with gastric cancer undergoing gastrectomy. Systematic review registration Identifier, CRD42023414678, https://www.crd.york.ac.uk/PROSPERO/.